2021
DOI: 10.3390/nursrep11020046
|View full text |Cite
|
Sign up to set email alerts
|

Learning Experience of Chinese Nursing Students during Clinical Practicum: A Descriptive Qualitative Study

Abstract: The change in clinical environment can have a significant impact on nursing students’ clinical learning and as a consequence, to their competency. Students’ learning experiences could provide important insights for improving the existing approach towards clinical education. This descriptive qualitative study aimed to explore nursing students’ clinical learning experience. Focus group interviews were conducted with 20 final year nursing students studying a bachelor nursing programme at a self-financing tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…Target users were involved to elucidate the challenges related to clinical practice from the perspectives of NSs, NPs, and NEs. The development process also used the results of earlier studies on the challenges in guiding NSs in clinical education [ 12 , 17 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Target users were involved to elucidate the challenges related to clinical practice from the perspectives of NSs, NPs, and NEs. The development process also used the results of earlier studies on the challenges in guiding NSs in clinical education [ 12 , 17 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…We invited user representatives (NSs, NPs, and NEs) to participate in developing our technology-supported guidance model, an approach that research indicates brings both advantages and challenges [47,48]. One advantage was that our user representatives recognized and confirmed that their challenges in nursing education in clinical practice were identical to those reported in research studies [7,17,28]. Our user representatives also underlined the need for an accessible solution compatible with their existing daily routines that provided positive input and reminders in daily clinical practice.…”
Section: Importance Of User Involvementmentioning
confidence: 98%
See 1 more Smart Citation
“…A positive work environment with personalization is an important element for a positive work environment [ 39 ]. In addition, as the study by Tang [ 6 ] mentioned, encountering a variety of patients with different illnesses is highly challenging for nursing students. The conflict created by the differences between the actual and expected illness manifestations can cause anxiety in student nurses.…”
Section: Discussionmentioning
confidence: 99%
“…When practicing nursing care, anxiety-inducing situations might interrupt the student nurse’s inner learning motives, ability to assist, and level of hard work [ 4 , 5 ]. Many nursing studies mentioned their anxiety status, whether or not they were stimulated by the clinical practicum situation [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%